STRATEGI PENGEMBANGAN USAHA AGROINDUSTRI SIRUP PARIJOTO (Medinilla speciosa) DI DESA COLO KECAMATAN DAWE KABUPATEN KUDUS - Istanto; Sri Wahyuningsih; Misbachul Munir (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2021)
The purpose of this research is to know the internal and external environment that affects the development of agroindustrial business and syrup Parijoto and formulate alternative strategies for business development of agroindustrial syrup Parijoto in Colo-Village district Dawe Kudu Regency. The methods used in location selection and sampling of respondents are purposive sampling. Total number of 24 respondents. Data analysis methods consist of first data analysis using Internal Factors Evaluation (IFE) and External Factors Evaluation (EFE), while second data analysis using SWOT matrix. The Total value of Matrik IFE is 3.11, this shows that the strength of the entrepreneurs of parijoto syrup is able to overcome the weakness. The Total value of Efe's matrix is 3.27, which shows that the opportunity of the Parijoto syrup entrepreneur is able to cope with the threat. Based on the construction of the matrix IE known that the business of Parijoto syrup in Colo village is in the area of cell I is growing and building, means the business of Parijoto syrup has the opportunity to continue to grow and continue to build. The strategies suitable for this area are market penetration, market development, and product development. The right alternative strategy for this endeavor is to use the power to capitalize on existing opportunities. Personal capital, quality produced products, have a PIRT and a halal label so that employers can run and improve its production business.